Curable resin composition, resin sheet, and cured product

By using alternating copolymerization of maleimide compounds and specific compounds in polymer materials, combining hardening accelerators and polymerization initiators, the problems of insufficient heat resistance and water resistance of existing materials in high temperature and high humidity environments are solved. A resin composition that achieves high heat resistance and low water absorption characteristics is suitable for sealing materials for modern electronic devices.

CN119278222APending Publication Date: 2025-01-07NIPPON KAYAKU CO LTD

Patent Information

Application Number
CN202380043305.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing polymer materials have insufficient heat resistance and water resistance in high temperature and high humidity environments, making it difficult to meet the demand for sealing materials of modern electronic devices, especially in the fields of 5G communications and automotive electronics.

Method used

A hardening resin composition has been developed, containing maleimide compounds and compounds with Q and e values ​​in a specific range, and its hardening properties and resistance are improved by alternating copolymerization and addition of hardening accelerators, polymerization initiators, etc. Heat and low water absorption properties.

Benefits of technology

It realizes high heat resistance and low water absorption characteristics, and is suitable for electronic equipment sealing materials in high temperature and high humidity environments, improving the heat resistance and dielectric characteristics of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278222A_ABST
    Figure CN119278222A_ABST
Patent Text Reader

Abstract

Provided is a curable resin composition having good curability, high heat resistance, and low water absorption characteristics. A curable resin composition containing: (A) a maleimide compound; and (B) a compound having, as a partial structure, a functional group in which the Q value, which is the stability index of the radical, and the e value, which is the polarity index of the radical, are within a specific range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] In recent years, laminated boards equipped with electrical and electronic components have been required to have a wide range of characteristics and to be more sophisticated due to the expansion of their application areas. The mainstream of existing semiconductor chips is mounted on metal lead frames, but semiconductor chips with high processing power such as central processing units (hereinafter referred to as CPUs (central processing units)) are mostly mounted on laminated boards made of polymer materials.

[0002] In particular, in semiconductor packages (hereinafter referred to as PKG) used in smart phones, in order to meet the requirements of miniaturization, thinning and high density, the PKG substrate is required to be thinner, but if the PKG substrate is thinner, the rigidity will decrease, so the heating when the PKG is soldered and mounted on the motherboard (printed circuit board (PCB)) will cause large warping and other undesirable conditions. In order to reduce the above-mentioned problems, a high Tg PKG substrate material above the soldering mounting temperature is required.

[0003] In addition, the fifth-generation communication system "5G", which is currently being developed at an accelerated pace, is expected to further promote large-capacity and high-speed communications. The demand for low dielectric loss tangent materials is increasing, and at least a dielectric loss tangent of 0.005 or less at 10GHz is required.

[0004] Furthermore, in the automotive field, electronicization is advancing, and sometimes precision electronic equipment is installed near the engine drive unit, which requires a higher level of heat and humidity resistance. SiC semiconductors are beginning to be used in electric vehicles and air conditioners, and the sealing materials for semiconductor elements require extremely high heat resistance, so existing epoxy resin sealing materials are no longer able to cope with it.

[0005] In this context, polymer materials that have both high heat resistance and low dielectric properties are being studied. For example, Patent Document 1 proposes a composition comprising a maleimide resin and a phenolic resin containing an acrylic group. However, on the other hand, since the phenolic hydroxyl groups that do not participate in the reaction remain during the curing reaction, it cannot be said that the electrical properties are sufficient. In addition, Patent Document 2 discloses an allyl ether resin that uses an allyl group to replace the hydroxyl group. However, it is shown that Claisen Rearrangement occurs at 190°C, and phenolic hydroxyl groups that do not contribute to the curing reaction are generated at a general substrate molding temperature of 200°C, so the electrical properties cannot be satisfied. In addition, any of these situations are derived from the phenolic hydroxyl groups that are polar groups, and the water absorption properties are likely to deteriorate, and improvements are expected.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Laid-Open No. 04-359911

[0009] Patent Document 2: International Publication No. 2016 / 002704 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The present invention has been made in view of the above-mentioned situation, and an object of the present invention is to provide a curable resin composition having high heat resistance and low water absorption properties.

[0012] Technical means of solving problems

[0013] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that a curable resin composition, i.e., a curable resin composition containing a maleimide compound and a compound having a Q value, which is an index of radical stability, and an e value, which is an index of radical polarity, within specific ranges, has excellent curability and its cured product has excellent high heat resistance and low water absorption properties, thereby completing the present invention.

[0014] That is, the present invention relates to the following [1] to [7]. In the present invention, "(numeric value 1) to (numeric value 2)" means that the upper and lower limits are included. [1]

[0016] A curable resin composition comprising:

[0017] (A) a maleimide compound; and

[0018] (B) Compounds having a Q value of 0 to 1.0 and an e value of -2.0 to 0.7. [2]

[0020] The curable resin composition according to the aforementioned item [1], wherein the component (B) is a compound having an aromatic ring in its molecule. [3]

[0022] The curable resin composition according to the aforementioned item [1], wherein the component (B) is a compound represented by the following formula (4).

[0023] [Chemistry 1]

[0024]

[0025] (In formula (4), X represents a functional group having an ethylenically unsaturated double bond or an acetylenically unsaturated triple bond, Ar represents a benzene ring or a naphthalene ring; Y represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms; and k represents an integer of 1 to 4) [4]

[0027] The curable resin composition according to the aforementioned item [1], wherein the component (A) is a compound represented by the following formula (1).

[0028] [Chemistry 2]

[0029]

[0030] (In formula (1), X independently represents any one of the structures represented by the following formulas (2-a) to (2-c); R represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, or a halogenated alkyl group; m represents an integer of 1 to 3, n is a repetition number, and the average value of n is n ave 1<n ave <10)

[0031] [Chemistry 3]

[0032]

[0033] (In formula (2-a) to formula (2-c), * represents a bond to a benzene ring; R2 each independently represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms; and q each independently represents an integer of 1 to 4) [5]

[0035] The curable resin composition according to any one of the above items [1] to [4], further comprising a polymerization initiator. [6]

[0037] A resin sheet comprising the curable resin composition according to any one of the above items [1] to [5] and a support. [7]

[0039] A cured product, which is a cured product of the curable resin composition according to any one of the above items [1] to [5].

[0040] Effects of the Invention

[0041] According to the present invention, a curable resin composition having excellent curability, high heat resistance, and low water absorption characteristics and a cured product thereof can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] [ Figure 1 ] represents the GPC chart of Synthesis Example 1.

[0043] [ Figure 2 ] represents the HPLC chart of Synthesis Example 1.

[0044] [ Figure 3 ] represents the 1 H-NMR chart.

[0045] [ Figure 4] represents the DMA chart of Example 1 and Comparative Example 1.

[0046] [ Figure 5 ] represents the DSC charts of Examples 3 to 5.

[0047] [ Figure 6 ] shows the DSC charts of Comparative Examples 3 to 5. DETAILED DESCRIPTION

[0048] The curable resin composition of the present invention contains: (A) a maleimide compound (hereinafter, also referred to as component (A)); and (B) a compound having a Q value of 0 to 1.0 and an e value of -2.0 to 0.7 (hereinafter, also referred to as component (B)).

[0049] The so-called component (A) of the present invention, that is, the maleimide compound, refers to a compound having one or more maleimide groups in the molecule. As component (A), for example, 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide, metaphenylene bismaleimide, 2,2'-bis〔4-(4-maleimide phenoxy) phenyl〕propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenyl sulfone bismaleimide, 1,3-bis(3-maleimide phenoxy) benzene, 1,3-bis(4-maleimide phenoxy) benzene, neophenol (Xyloc) type maleimide compounds (Annelis ( Anilix) maleimide, manufactured by Mitsui Chemicals Fine Chemicals Co., Ltd.), biphenyl aralkyl type maleimide compound (solidified by distilling off the resin solution containing the maleimide compound (M2) described in Example 4 of Japanese Patent Publication No. 2009-001783 under reduced pressure), bisaminocumylbenzene type maleimide (maleimide compound described in International Publication No. 2020 / 054601 and the compound represented by the following formula (3)), maleimide compound having an indane structure described in Japanese Patent No. 6629692 or International Publication No. 2020 / 217679, "Material Stage (MATERIAL STAGE (MATERIAL STAGE (MATERIAL STAGE (MATERIAL STAGE (MATERIAL STAGE (MATERIAL STAGE (MATERIAL STAGE The maleimide compounds described in "MATERIAL STAGE)" Vοl.18, No.12 2019 "~Continued·Epoxy Resin CAS Number Terminology~Hardener CAS Number Memorandum No. 31 Bismaleimide (1)" or "MATERIAL STAGE" Vοl.19, No.2 2019 "~Continued·Epoxy Resin CAS Number Terminology~Hardener CAS Number Memorandum No. 32 Bismaleimide (2)", etc., are not limited to these. In addition, these may be used alone or in combination of two or more.

[0050] From the viewpoints of solvent solubility, dielectric properties, and heat resistance, the component (A) of the present invention is preferably a maleimide compound having a phenylmaleimide structure, and more preferably represented by the following formula (1).

[0051] [Chemistry 4]

[0052]

[0053] In formula (1), X is independently any one of the structures represented by formula (2-a) to formula (2-c) below. R is a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, or a halogenated alkyl group, and is particularly preferably a hydrogen atom. n is the number of repetitions, and the average value of n is n ave 1<n ave <10. ave The value of can be calculated from the value of the weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) of the maleimide resin.

[0054] [Chemistry 5]

[0055]

[0056] In formulae (2-a) to (2-c), * represents a bond to a benzene ring. R2 each independently represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms, and a hydrogen atom is particularly preferred. q each independently represents an integer of 1 to 4.

[0057] When X in the formula (1) is particularly preferably a structure represented by the formula (2-b), it can be represented by the following formula (3).

[0058] [Chemistry 6]

[0059]

[0060] In formula (3), R represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, or a halogenated alkyl group, and is particularly preferably a hydrogen atom. n is the number of repetitions, and the average value of n is ave 1<n ave <10. ave The value of can be calculated from the value of the weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) measurement of the maleimide resin.

[0061] The component (B) of the present invention is a compound having a Q value of 0 to 1.0 and an e value of -2.0 to 0.7. The Q value is more preferably 0.03 to 0.8, and the e value is more preferably -2.0 to 0.5.

[0062] The Q value and e value of the present invention are based on the Q theory and e theory of Alfrey and Price. Although they are empirical, they quantitatively express the situation that the reactivity in the polymerization reaction of vinyl compounds is determined by the polarizability of the substituents and the resonance effect (and stereo factor). There are general polymer textbooks such as "Polymer Chemistry" (Kyoritsu Publishing, edited by Shunsuke Murahashi, pages 75 to 77), and the Q value and e value of various monomers are calculated based on styrene. The Q value is an index representing the stability of free radicals. When the Q value is small, the free radical becomes unstable, so the reactivity tends to become good. The e value is an index representing the polarity (electrical deviation) of the free radical. When the values ​​of the monomers are greatly different, especially when they are a combination of positive and negative signs, copolymerization is easy.

[0063] Component (B) preferably has an aromatic ring in the molecule. As the aromatic ring, for example, there can be listed: benzene ring, biphenyl ring, naphthalene ring, indene ring, terphenyl ring (terphenyl ring), acenaphthene ring, fluorene ring, phenalene ring (phenalene ring), phenanthrene ring (phenanthrene ring), anthracene ring, etc. From the viewpoint of Q value and e value, in the case of a compound having a benzene ring, naphthalene ring, or acenaphthene ring, by combining a maleimide compound, the curability is improved, so it is particularly preferred. For example, the e value of phenylmaleimide (partial structure of aromatic maleimide) is 3.24, and the e value of acenaphthene is -1.88. Since the difference in the electron density of the olefins in each functional group is very large, a high curing promotion effect can be expected.

[0064] In addition, component (B) is preferably represented by the following formula (4).

[0065] [Chemistry 7]

[0066]

[0067] (In formula (4), X represents a functional group having an ethylenically unsaturated double bond or an acetylenically unsaturated triple bond, Ar represents a benzene ring or a naphthalene ring; Y represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms; and k represents an integer of 1 to 4)

[0068] X in the formula (4) is preferably represented by the following formula (a) to (e), and more preferably has a functional group represented by the following formula (a) to (c).

[0069] [Chemistry 8]

[0070]

[0071] (In formula (a) to formula (e), * represents the bonding position with Ar in formula (4); when there are two *, it represents the bonding with two carbon atoms on the benzene ring or naphthalene ring)

[0072] The compound represented by formula (4) is preferably acenaphthene. As acenaphthene, a substance refined from coal tar can be used, and a substance synthesized by dehydrogenation of acenaphthenylnaphthalene or dehydration of 1-acenaphthenol can also be used. Examples of commercially available acenaphthene include acenaphthene from JFE Chemical Co., Ltd.

[0073] The content of component (A) is 1 part by mass or more and 1000 parts by mass or less, more preferably 5 parts by mass or more and 500 parts by mass or less, and further preferably 10 parts by mass or more and 300 parts by mass or less, relative to 100 parts by mass of component (B). In the case of the above range, the electron-deficient olefin of maleimide and the electron-rich olefin of component (B) are easily alternately copolymerized, and the curability is improved, so it is also preferred from the viewpoint of improving heat resistance.

[0074] [Hardening accelerator]

[0075] The curable resin composition of the present invention can also be cured by adding a curing accelerator. The curing accelerator is preferably an anionic curing accelerator that generates anions by irradiation with ultraviolet light or visible light or heating to accelerate the curing reaction, or a cationic curing accelerator that generates cations by irradiation with ultraviolet light or visible light or heating to accelerate the curing reaction.

[0076] Examples of anionic curing accelerators include imidazoles such as 2-methylimidazole, 2-ethylimidazole, and 2-ethyl-4-methylimidazole; trialkylamines such as triethylamine and tributylamine; 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, preferably 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene. In addition, examples include phosphines such as triphenylphosphine, tetrabutylammonium salts, triisopropylmethylammonium salts, trimethyldecylammonium salts, hexadecyltrimethylammonium salts, and quaternary ammonium salts such as hexadecyltrimethylammonium hydroxide, but are not limited thereto. In addition, these may be used alone or in combination.

[0077] Examples of the cationic hardening accelerator include quaternary phosphonium salts such as triphenylbenzylphosphonium salt, triphenylethylphosphonium salt, and tetrabutylphosphonium salt (the counter ions of the quaternary salts are halogen, organic acid radical ions, hydroxide ions, etc., which are not particularly specified, and organic acid radical ions and hydroxide ions are particularly preferred), tin octylate, zinc carboxylates (zinc 2-ethylhexanoate, zinc stearate, zinc behenate, zinc myristate), and transition metal compounds (transition metal salts) such as zinc phosphates (zinc octyl phosphate, zinc stearyl phosphate), but are not limited to these. In addition, these may be used alone or in combination of a plurality of types.

[0078] When the total amount of the component (A) and the component (B) is 100 parts by mass, the amount of the curing accelerator to be added is 0.01 to 5.0 parts by mass as necessary.

[0079] [Inorganic filler]

[0080] The curable resin composition of the present invention may contain an inorganic filler. Examples of the inorganic filler include fused silica, crystalline silica, porous silica, alumina, zircon, calcium silicate, calcium carbonate, quartz powder, silicon carbide, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, forsterite, steatite, spinel, mullite, titanium dioxide, talc, clay, iron oxide, asbestos, glass powder and other powders, or inorganic fillers made of these in a spherical or crushed form, but are not limited to these. In addition, these may be used alone or in combination of multiple types.

[0081] The amount of the inorganic filler used in obtaining a curable resin composition for semiconductor sealing is preferably 80 to 92 parts by mass, and more preferably 83 to 90 parts by mass, based on 100 parts by mass of the curable resin composition. In addition, when obtaining a curable resin composition for an interlayer insulating layer forming material, a copper sheet laminate or prepreg, a substrate material such as RCC, the amount of the inorganic filler used is preferably 5 to 80 parts by mass, and more preferably 10 to 60 parts by mass, based on 100 parts by mass of the curable resin composition.

[0082] [Polymerization initiator]

[0083] The curable resin composition of the present invention can also improve the curability by adding a polymerization initiator. The so-called polymerization initiator refers to a compound that can polymerize olefin functional groups such as ethylenic unsaturated bonds, and examples thereof include olefin metathesis polymerization initiators, anionic polymerization initiators, cationic polymerization initiators, free radical polymerization initiators, etc. Among them, it is preferred to use a free radical polymerization initiator with curability and appropriate stability. The so-called free radical polymerization initiator refers to a compound that generates free radicals and starts a chain polymerization reaction by irradiation or heating with ultraviolet or visible light. As the free radical polymerization initiator that can be used, organic peroxides, azo compounds, benzopinacols, etc. can be listed. Organic peroxides are preferably used because they have little effect on curing temperature control or exhaust gas suppression, and the decomposition products have little effect on electrical properties.

[0084] Examples of the organic peroxide include ketone peroxides such as methyl ethyl ketone peroxide and acetylacetone peroxide; diacyl peroxides such as benzoyl peroxide; dialkyl peroxides such as dicumyl peroxide and 1,3-bis(tert-butylperoxyisopropyl)benzene; peroxyketals such as tert-butyl peroxybenzoate and 1,1-di-tert-butylperoxycyclohexane; α-cumyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate; Alkyl peroxy esters such as tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-amyl peroxybenzoate; peroxy carbonates such as di-2-ethylhexyl peroxydicarbonate, bis (4-tert-butylcyclohexyl) peroxydicarbonate, tert-butyl peroxyisopropyl carbonate, 1,6-bis (tert-butylperoxycarbonyloxy) hexane; tert-butyl hydroperoxide, cumene hydroperoxide, tert-butyl peroxyoctanoate, lauroyl peroxide, etc., but are not limited to these. In addition, these can be used alone or in combination. Among the organic peroxides, ketone peroxides, diacyl peroxides, hydroperoxides, dialkyl peroxides, peroxyketals, alkyl peroxy esters, peroxycarbonates, etc. are preferred, and dialkyl peroxides are more preferred.

[0085] Examples of the azo compound include, but are not limited to, azobisisobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(2,4-dimethylvaleronitrile). These may be used alone or in combination of two or more.

[0086] The amount of the polymerization initiator added is preferably 0.01 to 5 parts by mass, particularly preferably 0.01 to 3 parts by mass, relative to 100 parts by mass of the curable resin composition. If the amount of the polymerization initiator used is less than 0.01 parts by mass, the molecular weight may not be sufficiently extended during the polymerization reaction, and if it is more than 5 parts by mass, the dielectric properties such as the dielectric constant and the dielectric loss tangent may be impaired.

[0087] [Polymerization Inhibitor]

[0088] The curable resin composition of the present invention may contain a polymerization inhibitor. By containing a polymerization inhibitor, the storage stability can be improved and the reaction start temperature can be controlled. By controlling the reaction start temperature, it is easy to ensure fluidity, and it becomes easy to perform B-stage such as prepreg without impairing the impregnation property in glass fiber cloth, etc. If the polymerization reaction proceeds excessively during prepreg, it is easy to cause disadvantages such as lamination becoming difficult in the lamination process.

[0089] The polymerization inhibitor may be added during or after the synthesis of component (A). The amount of the polymerization inhibitor used is 0.008 to 1 part by weight, preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight of component (A).

[0090] Examples of polymerization inhibitors include phenolic, sulfuric, phosphorus, hindered amine, nitroso, and nitroxyl radical inhibitors. One polymerization inhibitor may be used alone, or multiple polymerization inhibitors may be used in combination. Among these, phenolic, hindered amine, nitroso, and nitroxyl radical inhibitors are preferred in the present invention.

[0091] Examples of the phenolic polymerization inhibitor include monophenols such as 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-p-ethylphenol, stearyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, isooctyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylaniline)-1,3,5-triazine, 2,4-bis[(octylthio)methyl]-o-cresol, and 2,2′-methylenebis(4-methyl)-1,3,5-triazine. -6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid), 2,2'-thio-diethylene Bisphenols such as bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 3,5-di-tert-butyl-4-hydroxybenzyl phosphate-diethyl ester, 3,9-bis[1,1-dimethyl-2-{β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionyloxy}ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane, and calcium bis(3,5-di-tert-butyl-4-hydroxybenzylsulfonate); 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4, 6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-tert-butylphenyl)butyrate]ethylene glycol ester, tris-(3,5-di-tert-butyl-4-hydroxybenzyl)-isocyanurate, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-s-triazine-2,4,6-(1H,3H,5H)trione, tocopherol and other high molecular weight phenols, but are not limited to these.

[0092] Examples of the sulfur-based polymerization inhibitor include, but are not limited to, dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, and distearyl 3,3'-thiodipropionate.

[0093] Examples of the phosphorus-based polymerization inhibitor include triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, tris(nonylphenyl) phosphite, pentaerythritol diisodecyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, cyclic neopentanetetraylbis(octadecyl)phosphite, cyclic neopentanetetraylbis(2,4-di-tert-butylphenyl)phosphite, cyclic neopentanetetraylbis(2,4-di-tert-butylphenyl)phosphite, bis[2- Phosphites such as tert-butyl-6-methyl-4-{2-(octadecyloxycarbonyl)ethyl}phenyl]hydrogen phosphite, oxaphosphaphenanthrene oxides such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5-di-tert-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, but are not limited to these.

[0094] Examples of the hindered amine polymerization inhibitor include Adekastab LA-40MP, Adekastab LA-40Si, Adekastab LA-402AF, Adekastab LA-87, Adekastab LA-82, Adekastab LA-81, Adekastab LA-77Y, Adekastab LA-77G, Adekastab LA-72, Adekastab LA-68, and Adekastab LA-63P, Adekastab LA-57, Adekastab LA-52, Chimassorb 2020FDL, Chimassorb 944FDL, Chimassorb 944LD, Tinuvin 622SF, Tinuvin PA144, Tinuvin 765, Tinuvin 770DF, Tinuvin XT55FB, Tinuvin 111FDL, Tinuvin 783FDL, Tinuvin 791FB, etc., but not limited to these.

[0095] Examples of the nitroso polymerization inhibitor include, but are not limited to, p-nitrosophenol, N-nitrosodiphenylamine, and ammonium salts of N-nitrosophenylhydroxylamine (cupferron). Among these, ammonium salts of N-nitrosophenylhydroxylamine (cupferron) are preferred.

[0096] Examples of the nitroxyl radical polymerization inhibitor include, but are not limited to, di-tert-butyl nitroxide, 2,2,6,6-tetramethylpiperidin-1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl, 4-oxo-2,2,6,6-tetramethylpiperidin-1-oxyl, 4-amino-2,2,6,6-tetramethylpiperidin-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidin-1-oxyl, 4-acetoxy-2,2,6,6-tetramethylpiperidin-1-oxyl, and 4-benzoyloxy-2,2,6,6-tetramethylpiperidin-1-oxyl.

[0097] [Flame retardant]

[0098] The curable resin composition of the present invention may contain a flame retardant, for example, a halogen flame retardant, an inorganic flame retardant (antimony compounds, metal hydroxides, nitrogen compounds, boron compounds, etc.), a phosphorus flame retardant, etc., and from the viewpoint of achieving halogen-free flame retardancy, a phosphorus flame retardant is preferred.

[0099] As the phosphorus flame retardant, it can be a reactive type or an additive type. As a specific example, it can be listed: trimethyl phosphate, triethyl phosphate, tritolyl phosphate, tri(xylyl) phosphate, tolyl diphenyl phosphate, tolyl-2,6-di(xylyl) phosphate, 1,3-phenylene bis(di(xylyl) phosphate), 1,4-phenylene bis(di(xylyl) phosphate), 4,4'-biphenyl (di(xylyl) phosphate) and other phosphates; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide and other phosphanes, in addition to which phosphorus-containing epoxy compounds, red phosphorus, etc. obtained by reacting epoxy resin with the active hydrogen of the phosphanes can be listed, but they are not limited to these. In addition, these can be used alone or in combination. Among the above-mentioned exemplified substances, phosphates, phosphanes or phosphorus-containing epoxy compounds are preferred, and 1,3-phenylenebis(di(xylyl)phosphate), 1,4-phenylenebis(di(xylyl)phosphate), 4,4′-biphenyl(di(xylyl)phosphate) or phosphorus-containing epoxy compounds are particularly preferred.

[0100] [Flame retardant]

[0101] When the total of component (A) and component (B) is 100 parts by mass, the content of the flame retardant is preferably in the range of 0.1 to 0.6 parts by mass. If it is less than 0.1 parts by mass, the flame retardancy may be insufficient, and if it is more than 0.6 parts by mass, the hygroscopicity and dielectric properties of the cured product may be adversely affected.

[0102] [Light stabilizer]

[0103] The curable resin composition of the present invention can use a light stabilizer. As the light stabilizer, a hindered amine light stabilizer is preferred, and a hindered amine light stabilizer (HALS) is particularly preferred. As HALS, for example, there can be listed: a reaction product of dibutylamine-1,3,5-triazine-N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine, a reaction product of dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidinyl, poly{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4 [-piperidinyl) imino}], bis(1,2,2,6,6-pentamethyl-4-piperidinyl) [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl] methyl] butyl malonate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-n-butyl malonate, etc., but are not limited to these. In addition, these may be used alone or in combination of a plurality of types.

[0104] When the total of component (A) and component (B) is 100 parts by mass, the content of the light stabilizer is preferably in the range of 0.001 to 0.1 parts by mass. If it is less than 0.001 parts by mass, there is a risk that the light stabilization effect may not be sufficiently exhibited, and if it is more than 0.1 parts by mass, there is a risk that the hygroscopicity and dielectric properties of the cured product may be adversely affected.

[0105] [Binder resin]

[0106] The curable resin composition of the present invention can use a binder resin. Examples of the binder resin include butyral resins, acetal resins, acrylic resins, epoxy-nylon resins, nitrile butadiene rubber (NBR)-phenol resins, epoxy-NBR resins, silicone resins, etc., but are not limited to these. In addition, these can be used alone or in combination of multiple types.

[0107] The amount of the binder resin blended is preferably within a range that does not impair the flame retardancy and heat resistance of the cured product, and is preferably 0.05 to 50 parts by mass, based on 100 parts by mass of the total of component (A) and component (B), and more preferably 0.05 to 20 parts by mass as needed.

[0108] [additive]

[0109] The curable resin composition of the present invention may contain additives, such as modified acrylonitrile copolymers, polyethylene, fluororesins, silicone gels, silicone oils, surface treatment agents for fillers such as silane coupling agents, mold release agents, and colorants such as carbon black, phthalocyanine blue, and phthalocyanine green.

[0110] The amount of the additives added is preferably 1,000 parts by mass or less, more preferably 700 parts by mass or less, relative to 100 parts by mass of the curable resin composition.

[0111] The curable resin composition of the present invention can further use epoxy resin, active ester compound, phenol resin, polyphenylene ether compound, amine resin, compound with ethylenic unsaturated bond, isocyanate resin, polyamide resin, cyanate resin, polyimide resin, polybutadiene and its modified product, polystyrene and its modified product, etc., these can be used alone or in combination. Among these compounds, in terms of the balance of heat resistance, adhesion, and dielectric properties, it is preferred to contain polyphenylene ether compound, compound with ethylenic unsaturated bond, cyanate resin, polybutadiene and its modified product, polystyrene and its modified product. By containing these compounds, the brittleness of the hardened material can be improved and the adhesion to metal can be improved, and the cracks of the package in the reliability test such as reflow soldering or hot and cold cycle can be suppressed.

[0112] About the usage amount of the compound, in the case of no special instructions, relative to the component (A), preferably less than 10 mass parts, and then preferably less than 5 mass parts, particularly preferably less than 3 mass parts. In addition, the preferred lower limit is more than 0.1 mass parts, more preferably more than 0.25 mass parts, and then preferably more than 0.5 mass parts. By being set to within the scope, the effect of each compound added can be attached while the effect of the heat resistance or dielectric properties of the component (A) is effectively utilized. About these components, the following exemplification can be used.

[0113] [Epoxy resin]

[0114] Preferred epoxy resins are exemplified below, but the epoxy resins are not limited thereto. The epoxy resin may be in a liquid or solid state, and may be used alone or in combination of two or more.

[0115] Examples of the liquid epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol AF epoxy resin, naphthalene epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, phenol novolac epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane epoxy resin, cyclohexanedimethanol epoxy resin, and epoxy resin having a butadiene structure. Specific examples include: "RE310S", "RE410S" (all manufactured by Nippon Kayaku Co., Ltd., bisphenol A type epoxy resin), "RE303S", "RE304S", "RE403S", "RE404S" (all manufactured by Nippon Kayaku Co., Ltd., bisphenol F type epoxy resin), "HP4032", "HP4032D", "HP4032SS" (all manufactured by DIC Corporation, naphthalene type epoxy resin), "828US", "jER828EL", "825", "828EL" (All bisphenol A epoxy resins manufactured by Mitsubishi Chemical Corporation), "jE807", "1750" (All bisphenol F epoxy resins manufactured by Mitsubishi Chemical Corporation), "jER152" (Phenol novolac epoxy resin manufactured by Mitsubishi Chemical Corporation), "630", "630LSD" (All glycidylamine epoxy resins manufactured by Mitsubishi Chemical Corporation), "ZX1059" (Mixture of bisphenol A epoxy resin and bisphenol F epoxy resin manufactured by Nippon Steel & Sumitomo Metal Chemicals), "EX-721" (Nagase Chemicals ChemteX, a glycidyl ester epoxy resin), "Celloxide 2021P" (a Daicel company, an alicyclic epoxy resin with an ester skeleton), "PB-3600" (a Daicel company, an epoxy resin with a butadiene structure), "ZX1658", "ZX1658GS" (the above are manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., liquid 1,4-glycidylcyclohexane epoxy resins), etc. These may be used alone or in combination of two or more.

[0116] Preferred solid epoxy resins include, for example, biphenylol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, and tetraphenylethane-type epoxy resins. Examples thereof include naphthol-type epoxy resins, bisphenol AF-type epoxy resins, naphthalene-type epoxy resins, and biphenyl-type epoxy resins.Specific examples include: "HP4032H" (manufactured by DIC Corporation, naphthalene-type epoxy resin), "HP-4700", "HP-4710" (the above are manufactured by DIC Corporation, naphthalene-type tetrafunctional epoxy resins), "N-690" (manufactured by DIC Corporation, cresol novolac-type epoxy resin), "N-695" (manufactured by DIC Corporation, cresol novolac-type epoxy resin), "HP-7200", "HP-7200HH", "HP- 7200H" (all manufactured by DIC, dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP-6000" (all manufactured by DIC, naphthylene ether type epoxy resin), "EPPN-502H" (manufactured by Nippon Kayaku Co., Ltd., trisphenol type epoxy resin), "NC-7000L", "NC-7300" (manufactured by Nippon Kayaku Co., Ltd., "NC-3000H", "NC-3000", "NC-3000L", "NC-3100" (all manufactured by Nippon Kayaku Co., Ltd., biphenyl aralkyl type epoxy resin), "XD-1000-2L", "XD-1000-L", "XD-1000-H", "XD-1000-H" (all manufactured by Nippon Kayaku Co., Ltd., dicyclopentadiene type epoxy resin), "ESN475V" (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., Naphthol epoxy resin), "ESN485" (manufactured by Nippon Steel & Sumitomo Metal Chemicals, naphthol novolac epoxy resin), "YX-4000H", "YX-4000", "YL6121" (manufactured by Mitsubishi Chemical, biphenyl epoxy resin), "YX-4000HK" (manufactured by Mitsubishi Chemical, dimethylphenol epoxy resin), "YX-8800" (manufactured by Mitsubishi Chemical, anthracene epoxy resin), "PG-100", "CG-500" (manufactured by Osaka Gas Chemical, Gas Chemicals, fluorene-based epoxy resin), "YL-7760" (manufactured by Mitsubishi Chemical Corporation, bisphenol AF type epoxy resin), "YL-7800" (manufactured by Mitsubishi Chemical Corporation, fluorene type epoxy resin), "jER1010" (manufactured by Mitsubishi Chemical Corporation, solid bisphenol A type epoxy resin), "jER1031S" (manufactured by Mitsubishi Chemical Corporation, tetraphenylethane type epoxy resin), etc. These may be used alone or in combination of two or more.

[0117] [Active ester compound]

[0118] So-called active ester compound refers to a compound containing at least one ester bond in a structure and having aliphatic chains, aliphatic rings or aromatic rings bonded on both sides of the ester bond. As active ester compounds, for example, phenol esters, thiophenol esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc., have two or more ester groups with high reactive activity in one molecule, which can be obtained by the condensation reaction of at least one compound of carboxylic acid compounds, acid chlorides or thiocarboxylic acid compounds and at least one compound of hydroxy compounds or thiol compounds. In particular, from the viewpoint of heat resistance improvement, it is preferably obtained from carboxylic acid compounds or acid chlorides and hydroxy compounds, as hydroxy compounds, preferably phenol compounds or naphthol compounds. Active ester compounds can be used alone or in combination of two or more.

[0119] Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.

[0120] Examples of the acid chloride include acetyl chloride, acryloyl chloride, methacryloyl chloride, malonyl chloride, succinyl dichloride, diglycolyl chloride, glutaryl dichloride, suberyl dichloride, sebacoyl dichloride, adipoyl dichloride, dodecanedioyl dichloride, azelaoyl chloride, 2,5-furandicarbonyl dichloride, phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, bis(4-chlorocarbonylphenyl) ether, 4,4'-diphenyldicarbonyl chloride, and 4,4'-azobisbenzoyl dichloride.

[0121] Examples of the phenol compound and the naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalin, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, pyrogallol, dicyclopentadiene-type diphenol compounds, phenol novolac, and phenol resins described below. Here, the so-called "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol in one molecule of dicyclopentadiene.

[0122] As preferred specific examples of active ester compounds, active ester compounds comprising dicyclopentadiene-type diphenol structures, active ester compounds comprising naphthalene structures, active ester compounds comprising acetylated products of phenol novolacs, active ester compounds comprising benzoylated products of phenol novolacs, compounds described in Example 2 of International Publication No. 2020 / 095829, and compounds disclosed in International Publication No. 2020 / 059625, etc., can be cited. Among them, active ester compounds comprising naphthalene structures and active ester compounds comprising dicyclopentadiene-type diphenol structures are more preferred. The so-called dicyclopentadiene-type diphenol structure represents a divalent structural unit comprising phenylene-dicyclopentylene-phenylene.

[0123] Examples of commercially available active ester compounds include: "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L-65TM", and "EXB-8150-65T" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure; and "EXB9416-70BK" (manufactured by DIC Corporation) as an active ester compound containing a naphthalene structure. ; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing an acetylated product of phenol novolac; "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester compounds containing a benzoylated product of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester hardener for an acetylated product of phenol novolac; "EXB-9050L-62M" manufactured by DIC Corporation as an active ester hardener containing a phosphorus atom, etc.

[0124] Regarding the mixing ratio of the active ester compound and the epoxy resin, the ratio (α / β) of the active ester equivalent (α) to the epoxy equivalent (β) is preferably 0.5 to 1.5, more preferably 0.8 to 1.2, and still more preferably 0.90 to 1.10. If it is out of the above range, there is a possibility that excess epoxy groups or active ester groups remain in the system, and the characteristics may be deteriorated in a high temperature storage test (150° C., 1000 hours, etc.) or a long-term reliability test under high temperature and high humidity conditions (temperature: 85° C., humidity: 85%, etc.).

[0125] [Phenolic resin]

[0126] The so-called phenol resin is a compound having two or more phenolic hydroxyl groups in the molecule. As the phenol resin, for example, the reaction product of phenols and aldehydes, the reaction product of phenols and diene compounds, the reaction product of phenols and ketones, the reaction product of phenols and substituted biphenyls, the reaction product of phenols and substituted phenyls, the reaction product of bisphenols and aldehydes, etc. can be listed, but it is not limited to these. In addition, these can be used alone or in combination of multiple types.

[0127] Specific examples of the above-mentioned raw materials are shown below, but the raw materials are not limited to these.

[0128] <Phenols>

[0129] Phenol, alkyl-substituted phenol, aromatic-substituted phenol, hydroquinone, resorcinol, naphthol, alkyl-substituted naphthol, dihydroxybenzene, alkyl-substituted dihydroxybenzene, dihydroxynaphthalene, etc.

[0130] <Aldehydes>

[0131] Formaldehyde, acetaldehyde, alkyl aldehydes, benzaldehyde, alkyl-substituted benzaldehyde, hydroxybenzaldehyde, naphthaldehyde, glutaraldehyde, o-phthalaldehyde, crotonaldehyde, cinnamaldehyde, furfural, etc.

[0132] <Diene compounds>

[0133] Dicyclopentadiene, terpenes, vinylcyclohexene, norbornadiene, vinylnorbornene, tetrahydroindene, divinylbenzene, divinylbiphenyl, diisopropenylbiphenyl, butadiene, isoprene, etc.

[0134] <Ketones>

[0135] Acetone, methyl ethyl ketone, methyl isobutyl ketone, acetophenone, benzophenone, fluorenone, etc.

[0136] <Substituted biphenyls>

[0137] 4,4'-bis(chloromethyl)-1,1'-biphenyl, 4,4'-bis(methoxymethyl)-1,1'-biphenyl, 4,4'-bis(hydroxymethyl)-1,1'-biphenyl, etc.

[0138] <Substituted phenyl groups>

[0139] 1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene, 1,4-bis(hydroxymethyl)benzene, etc.

[0140] [Polyphenylene ether compound]

[0141] As the polyphenylene ether compound, from the viewpoint of heat resistance and electrical properties, a polyphenylene ether compound having an ethylenic unsaturated bond is preferred, and a polyphenylene ether compound having an acrylic group, a methacrylic group or a styrene structure is further preferred. As commercially available products, SA-9000 (manufactured by Saudi Basic Industries (SABIC), a polyphenylene ether compound having a methacrylic group) and OPE-2St 1200 (manufactured by Mitsubishi Gas Chemical Co., Ltd., a polyphenylene ether compound having a styrene structure) etc. can be cited.

[0142] The number average molecular weight (Mn) of the polyphenylene ether compound is preferably 500 to 5000, more preferably 2000 to 5000, and more preferably 2000 to 4000. If the molecular weight is less than 500, the heat resistance of the cured product tends to be insufficient. In addition, if the molecular weight is greater than 5000, the melt viscosity becomes high, and sufficient fluidity cannot be obtained, so there is a tendency to be poorly formed. In addition, the reactivity is also reduced, the curing reaction requires a long time, the amount of unreacted substances that do not enter the curing system increases, the glass transition temperature of the cured product decreases, and the heat resistance of the cured product tends to decrease.

[0143] When the number average molecular weight of the polyphenylene ether compound is 500 to 5000, it is possible to maintain excellent dielectric properties while exhibiting excellent heat resistance and moldability, etc. The number average molecular weight here can be specifically measured using gel permeation chromatography or the like.

[0144] The polyphenylene ether compound may be obtained by polymerization reaction, or may be obtained by redistributing a polyphenylene ether compound having a high molecular weight of about 10,000 to 30,000. In addition, free radical polymerizability may be imparted by reacting these as raw materials with compounds having ethylenically unsaturated bonds such as methacryloyl chloride, acryloyl chloride, chloromethylstyrene, etc. The polyphenylene ether compound obtained by redistribution reaction may be obtained by, for example, heating a high molecular weight polyphenylene ether compound in a solvent such as toluene in the presence of a phenol compound and a free radical initiator and performing a redistribution reaction. The polyphenylene ether compound obtained by the redistribution reaction has hydroxyl groups derived from phenolic compounds that contribute to hardening at both ends of the molecular chain, so that not only higher heat resistance can be maintained, but also functional groups can be introduced at both ends of the molecular chain after modification using a compound having ethylenically unsaturated bonds, which is preferred in terms of the above aspect. In addition, the polyphenylene ether compound obtained by polymerization reaction shows excellent fluidity, which is preferred in terms of the above aspect.

[0145] In the case of a polyphenylene ether compound obtained by a polymerization reaction, the molecular weight of the polyphenylene ether compound can be adjusted by adjusting the polymerization conditions, etc. In addition, in the case of a polyphenylene ether compound obtained by a redistribution reaction, the molecular weight of the obtained polyphenylene ether compound can be adjusted by adjusting the conditions of the redistribution reaction, etc. More specifically, it is considered to adjust the amount of the phenolic compound used in the redistribution reaction. That is, the more the amount of the phenolic compound is, the lower the molecular weight of the obtained polyphenylene ether compound. At this time, as a high molecular weight polyphenylene ether compound subjected to the redistribution reaction, poly (2,6-dimethyl-1,4-phenylene ether) can be used. In addition, as the phenolic compound used in the redistribution reaction, there is no particular limitation, and preferably a multifunctional phenolic compound having two or more phenolic hydroxyl groups in the molecule, such as bisphenol A, phenol novolac, cresol novolac, etc. can be used. These can be used alone or in combination of two or more.

[0146] The content of the polyphenylene ether compound is not particularly limited, and is preferably 5 to 1000 parts by mass, more preferably 10 to 750 parts by mass, when the total mass of component (A) and component (B) is 100 parts by mass. If the content of the polyphenylene ether compound is within the above range, a cured product having excellent heat resistance and the like and fully utilizing the excellent dielectric properties of the polyphenylene ether compound can be obtained, which is preferred in terms of the above aspect.

[0147] [Amine resin]

[0148] The so-called amine resin is a compound having two or more amino groups in the molecule. Examples of the amine resin include diaminodiphenylmethane, diaminodiphenylsulfone, isophoronediamine, naphthalene diamine, aniline novolac (a reaction product of aniline and formalin), N-methylaniline novolac (a reaction product of N-methylaniline and formalin), n-ethylaniline novolac (a reaction product of n-ethylaniline and formalin), a reaction product of 2-methylaniline and formalin, a reaction product of 2,6-diisopropylaniline and formalin, a reaction product of 2,6-diethylaniline and formalin, a reaction product of 2-ethyl-6-ethylaniline and formalin, a reaction product of 2,6-dimethylaniline and formalin, and a reaction product of aniline and dichloroxylene (xylylene) chloride), reaction products of aniline and substituted biphenyls (4,4'-bis(chloromethyl)-1,1'-biphenyl and 4,4'-bis(methoxymethyl)-1,1'-biphenyl, etc.) described in Japanese Patent No. 6429862, reaction products of aniline and substituted phenyls (1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene and 1,4-bis(hydroxymethyl)benzene, etc.), 4,4'-(1,3-phenylenediisopropylidene)dianiline, 4,4'-(1,4-phenylenediisopropylidene)dianiline, reaction products of aniline and diisopropenylbenzene, dimer diamine, etc., but are not limited to these. In addition, these may be used alone or in combination of two or more.

[0149] [Compounds containing ethylenically unsaturated bonds]

[0150] The ethylenically unsaturated bond-containing compound is a compound having one or more ethylenically unsaturated bonds in the molecule that can be polymerized by heat or light with or without the use of a polymerization initiator.

[0151] Examples of the compound containing an ethylenically unsaturated bond include reaction products of the phenol resin and a halogen compound containing an ethylenically unsaturated bond (chloromethylstyrene, allyl chloride, methylallyl chloride, acryloyl chloride, methacryloyl chloride, etc.); reaction products of phenols containing an ethylenically unsaturated bond (2-allylphenol, 2-propenylphenol, 4-allylphenol, 4-propenylphenol, eugenol, isoeugenol, etc.) and a halogen compound (1,4-bis(chloromethyl)benzene, 4,4'-bis(chloromethyl)biphenyl, 4,4'-difluorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-dibromobenzophenone, cyanuric chloride, etc.); reaction products of epoxy resins or alcohols and (meth)acrylic acids (acrylic acid, methacrylic acid, etc.); and acid-modified products thereof, but the present invention is not limited thereto. These may be used alone or in combination of two or more.

[0152] [Isocyanate resin]

[0153] The so-called isocyanate resin is a compound having two or more isocyanate groups in the molecule. Examples of the isocyanate resin include aromatic diisocyanates such as p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylene diisocyanate, m-xylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and naphthalene diisocyanate, diisocyanates of aliphatic or alicyclic structures such as isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hydrogenated xylene diisocyanate, norbornene diisocyanate, and lysine diisocyanate, polyisocyanates such as biuret bodies of isocyanate monomers or isocyanate bodies obtained by trimerizing the diisocyanate compounds, and polyisocyanates obtained by urethanization reaction of the isocyanate compounds with polyol compounds, but are not limited thereto. These may be used alone or in combination of two or more.

[0154] [Polyamide resin]

[0155] Examples of the polyamide resin include reaction products of one or more of diamine, diisocyanate, and oxazoline with dicarboxylic acid, reaction products of diamine and acid chloride, and ring-opening polymers of lactam compounds. These may be used alone or in combination of two or more.

[0156] Specific examples of the above-mentioned raw materials are shown below, but the raw materials are not limited to these.

[0157] <Diamine>

[0158] Ethylenediamine, trimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decanediamine, undecanediamine, dodecanediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,5-diaminopentane, 2-methyl-1,8-diaminooctane, dimer diamine, cyclohexanediamine, bis-(4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane, xylene diamine, norbornane diamine, isophorone diamine, bisaminomethyl tricyclodecane, phenylenediamine, diethyltoluenediamine, naphthalene diamine, diaminodiphenylmethane, bis(4-amino-3,5-dimethylphenyl)methane bis(4-amino-3,5-diethylphenyl)methane, 4,4'-methylenebis-o-toluidine, 4,4'-methylenebis-o-ethylaniline, 4,4'-methylenebis-2-ethyl-6-methylaniline, 4,4'-methylenebis-2,6-diisopropylaniline, 4,4-ethylenediphenylamine, diaminodiphenyl sulfone, diaminodiphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy) [4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-(1,3-phenylenediisopropylidene)dianiline, 4,4'-(1,4-phenylenediisopropylidene)dianiline, 9,9-bis(4-aminophenyl)fluorene, 2,7-diaminofluorene, aminobenzylamine, diaminobenzophenone, etc.

[0159] <Diisocyanate>

[0160] Phenyl diisocyanate, toluene diisocyanate, 1,3-bis(isocyanatomethyl)benzene, 1,3-bis(isocyanatomethyl)cyclohexane, bis(4-isocyanatophenyl)methane, isophorone diisocyanate, 1,3-bis(2-isocyanato-2-propyl)benzene, 2,2-bis(4-isocyanatophenyl)hexafluoropropane, dicyclohexylmethane-4,4'-diisocyanate, etc.

[0161] <Dicarboxylic acid>

[0162] Oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, terephthalic acid, isophthalic acid, 5-hydroxyisophthalic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, 5-sodium sulfonate of isophthalic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, cyclohexanedicarboxylic acid, biphenyldicarboxylic acid, naphthalene dicarboxylic acid, benzophenone dicarboxylic acid, furandicarboxylic acid, 4,4'-dicarboxy diphenyl ether, 4,4'-dicarboxy diphenyl sulfide, etc.

[0163] <Acid chloride>

[0164] Acetyl chloride, acryloyl chloride, methacryloyl chloride, malonyl chloride, succinyl chloride, diacetyl chloride oxide, glutaryl chloride, suberyl chloride, sebacoyl chloride, adipoyl chloride, dodecanedioyl chloride, azelayl chloride, 2,5-furandicarbonyl dichloride, phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, bis(4-chlorocarbonylphenyl) ether, 4,4'-diphenyldicarbonyl chloride, 4,4'-azodibenzoyl chloride, etc.

[0165] <Lactam>

[0166] ε-caprolactam, ω-undecanolactam, ω-laurolactam, etc.

[0167] [Polyimide resin]

[0168] As the polyimide resin, for example, a reaction product of the above-mentioned diamine and the tetracarboxylic dianhydride exemplified below can be mentioned, but it is not limited to these. In addition, these can be used alone or in combination of two or more.

[0169] <Tetracarboxylic dianhydride>

[0170] 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-cyclohexene-1,2-dicarboxylic anhydride, pyromellitic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, methylene-4,4'-diphthalic dianhydride, 1,1-ethylene-4,4'-diphthalic dianhydride, 2,2'-propylene-4,4'-diphthalic dianhydride, 1,2- Ethyl-4,4'-diphthalic dianhydride, 1,3-trimethylene-4,4'-diphthalic dianhydride, 1,4-tetramethylene-4,4'-diphthalic dianhydride, 1,5-pentamethylene-4,4'-diphthalic dianhydride, 4,4'-oxydiphthalic dianhydride, thio-4,4'-diphthalic dianhydride, sulfonyl-4,4'-diphthalic dianhydride, 1,3-bis(3,4-dicarboxyphenyl)phthalic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,3-bis[2-(3,4-dicarboxyphenyl)-2-propyl]phthalic dianhydride, 1,4-bis[2-(3,4-dicarboxyphenyl)-2 -propyl]phthalic anhydride, bis[3-(3,4-dicarboxyphenoxy)phenyl]methane dianhydride, bis[4-(3,4-dicarboxyphenoxy)phenyl]methane dianhydride, 2,2-bis[3-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, bis(3,4-dicarboxyphenoxy)dimethylsilane dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,3,3-tetramethyldisiloxane dianhydride, 2,3,6,7-naphthalenetetracarboxylic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, 1,2,5,6-naphthalenetetracarboxylic anhydride, 3,4,9,10-perylenetetracarboxylic anhydride, 2,3,6,7-anthracenetetracarboxylic anhydride, 1,2, 7,8-phenanthrenetetracarboxylic dianhydride, ethylenetetracarboxylic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, cyclopentanetetracarboxylic dianhydride, cyclohexane-1,2,3,4-tetracarboxylic dianhydride, cyclohexane-1,2,4,5-tetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, carbonyl-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, methylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 1,2-ethylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 1,1-ethylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 2,2-propylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, oxy-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, thio-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, sulfonyl-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, rel-[1S,5R,6R]-3-oxabicyclo[3,2 ,1] octane-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione), 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, ethylene glycol-bis-(3,4-dicarboxylic anhydride phenyl) ether, 4,4'-biphenyl bis(trimellitic acid monoester anhydride), 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride, etc. ,

[0171] [Cyanate ester resin]

[0172] The cyanate resin is a cyanate compound obtained by reacting a phenol resin with a cyanogen halide, and specific examples thereof include dicyanatobenzene, tricyanatobenzene, dicyanonaphthalene, dicyanobiphenyl, 2,2'-bis(4-cyanophenyl)propane, bis(4-cyanophenyl)methane, bis(3,5-dimethyl-4-cyanophenyl)methane, 2,2'-bis(3,5-dimethyl-4-cyanophenyl)propane, 2,2'-bis(4-cyanophenyl)ethane, 2,2'-bis(4-cyanophenyl)hexafluoropropane, bis(4-cyanophenyl)sulfone, bis(4-cyanophenyl)sulfide, phenol novolac cyanate, and a hydroxyl group of a phenol-dicyclopentadiene cocondensate converted into a cyanate group, but are not limited thereto. In addition, these may be used alone or in combination of a plurality of types.

[0173] In addition, the cyanate compound whose synthesis method is described in Japanese Patent Application Laid-Open No. 2005-264154 is particularly preferred as the cyanate compound because of its low hygroscopicity, flame retardancy, and excellent dielectric properties.

[0174] The cyanate resin may contain a catalyst such as zinc naphthenate, cobalt naphthenate, copper naphthenate, lead naphthenate, zinc octylate, tin octylate, lead acetylacetonate, or dibutyltin maleate in order to trimerize the cyanate group to form a s-triazine ring as necessary.

[0175] The catalyst is used in an amount of preferably 0.0001 to 0.10 parts by mass, more preferably 0.0001 to 0.0015 parts by mass, based on 100 parts by mass of the total mass of the cyanate resin, the component (A), and the component (B).

[0176] [Polybutadiene and its modified products]

[0177] Polybutadiene and its modified products are compounds having a polybutadiene or a structure derived from polybutadiene in the molecule. The structure derived from polybutadiene can convert part or all of the unsaturated bonds into single bonds by hydrogenation.

[0178] As polybutadiene and its modified product, for example, polybutadiene, hydroxyl-terminated polybutadiene, terminal (meth) acrylated polybutadiene, carboxylic acid-terminated polybutadiene, amine-terminated polybutadiene, styrene butadiene rubber, etc. can be cited, but it is not limited to these. In addition, these can use one, and multiple can also be used in combination. Among these, from the viewpoint of dielectric properties, polybutadiene or styrene butadiene rubber is preferred. As styrene butadiene rubber (Styrene Butadiene Rubber, SBR), for example, can be cited: RICON-100, RICON-181, RICON-184 (all manufactured by Cray Valley), 1,2-SBS (manufactured by Nippon Soda Co., Ltd.), etc., as polybutadiene, B-1000, B-2000, B-3000 (all manufactured by Nippon Soda Co., Ltd.), etc. can be cited. As the molecular weight of polybutadiene and styrene butadiene rubber, the weight average molecular weight is preferably 500 to 10000, more preferably 750 to 7500, and further preferably 1000 to 5000. Below the lower limit of the range, the amount of volatility is large, and it is difficult to adjust the solid content when the prepreg is made. Above the upper limit of the range, the compatibility with other curable resins deteriorates. In general, in the case of compounds containing heteroatoms such as oxygen or nitrogen such as bismaleimide or polymaleimide, it is difficult to ensure compatibility with low-polarity compounds such as compounds mainly containing hydrocarbons or compounds containing only hydrocarbons due to their polarity. On the other hand, component (A) of the present invention is also excellent in compatibility with materials having low polarity and low dielectric properties, or compounds containing only hydrocarbons, because it itself does not actively introduce a skeleton design of heteroatoms such as oxygen or nitrogen.

[0179] [Polystyrene and its modified products]

[0180] Polystyrene and its modified products are compounds having a structure of polystyrene or derived from polystyrene in the molecule.

[0181] Examples of polystyrene and modified products thereof include polystyrene, styrene-2-isopropenyl-2-oxazoline copolymer (Epocros RPS-1005 and RP-61 are both manufactured by Nippon Catalyst Co., Ltd.), SEP (styrene-ethylene-propylene copolymer: Septon 1020 manufactured by Kuraray Co., Ltd.), SEPS (styrene-ethylene-propylene-styrene copolymer: Septon 2002, Septon 2004F, Septon 2005, Septon 2006, Septon 2008, Septon 2009, Septon 2010, Septon 2011, Septon 2013, Septon 2014, Septon 2015, Septon 2016, Septon 2017, Septon 2018, Septon 2019, Septon 2020, Septon 2021, Septon 2023, Septon 2024, Septon 2025, Septon 2026, Septon 2027, Septon 2028, Septon 2029, Septon 2030, Septon 2031, Septon 2032, Septon 2033, Septon 2034, Septon 2035, Septon 2036, Septon 2037, Septon 2038, Septon 2039, Septon 2006, Septon 2063, Septon 2104 are all manufactured by Kuraray), SEEPS (styrene-ethylene / ethylene-propylene-styrene block copolymer: Septon 4003, Septon 4044, Septon 4055, Septon 4077, Septon 4099 are all manufactured by Kuraray), SEBS (styrene-ethylene-butylene-styrene block copolymer : Septon 8004, Septon 8006, Septon 8007L are all manufactured by Kuraray), SEEPS-ΟH (a compound having a hydroxyl group at the end of a styrene-ethylene / ethylene-propylene-styrene block copolymer: Septon HG252 is manufactured by Kuraray), SIS (styrene-isoprene-styrene block copolymer: Septon 5125, Septon 5127 are all manufactured by Kuraray) y) company), hydrogenated SIS (hydrogenated styrene-isoprene-styrene block copolymer: Hybrar 7125F, Hybrar 7311F are all manufactured by Kuraray), SIBS (styrene-isobutylene-styrene block copolymer: SIBSTAR073T, SIBSTAR102T, SIBSTAR103T (all manufactured by Kaneka Chemical), Septon V9827 (manufactured by Kuraray)), etc., but are not limited to these. In addition, these can be used alone or in combination. Polystyrene and its modified products have higher heat resistance and are not easily oxidized and degraded, so it is preferably not to have unsaturated bonds.In addition, the weight average molecular weight of polystyrene and its modified products is not particularly limited as long as it is 10,000 or more. However, if it is too large, the compatibility with low molecular weight components with a weight average molecular weight of about 50 to 1,000 and oligomer components with a weight average molecular weight of about 1,000 to 5,000, in addition to the polyphenylene ether compound, becomes poor, and it becomes difficult to ensure mixing and solvent stability. Therefore, it is preferably about 10,000 to 300,000.

[0182] The curable resin composition of the present invention can be obtained by preparing the above-mentioned components in a predetermined ratio, pre-curing at 130° C. to 180° C. for 30 seconds to 500 seconds, and then post-curing at 150° C. to 200° C. for 2 hours to 15 hours, thereby allowing a sufficient curing reaction to obtain a cured product of the present invention. Alternatively, the components of the curable resin composition may be uniformly dispersed or dissolved in a solvent or the like, and cured after removing the solvent.

[0183] The preparation method of the curable resin composition of the present invention is not particularly limited, and the components may be simply mixed uniformly, or prepolymerized. For example, prepolymerization is performed by heating a mixture of component (A) and component (B) in the presence or absence of a curing accelerator or a polymerization initiator, and in the presence or absence of a solvent. Similarly, amine compounds, compounds having ethylenically unsaturated bonds, maleimide compounds, cyanate compounds, polybutadiene and its modified products, polystyrene and its modified products, inorganic fillers and other additives may be added to perform prepolymerization. For mixing or prepolymerization of the components, for example, an extruder, a kneader, a roller, etc. are used in the absence of a solvent, and a reaction kettle with a stirring device is used in the presence of a solvent.

[0184] As a method for uniform mixing, the resin composition can be uniformly mixed by using a kneader, a roller, a planetary mixer or the like at a temperature in the range of 50°C to 100°C. The obtained resin composition can be crushed and then formed into a cylindrical ingot by a molding machine such as a tablet machine, or a granular powder or a powdery molded body, or the composition can be melted on a surface support and formed into a sheet with a thickness of 0.05mm to 10mm to form a curable resin composition molded body. The obtained molded body is a non-sticky molded body at 0°C to 20°C, and the fluidity and curability are hardly reduced even if stored at -25°C to 0°C for more than 1 week.

[0185] The obtained molded body can be molded into a hardened product using a transfer molding machine or a compression molding machine.

[0186] The curable resin composition of the present invention may also be a composition in the form of a varnish by adding an organic solvent (hereinafter referred to as varnish). The curable resin composition of the present invention may be dissolved in a solvent such as toluene, xylene, acetone, methyl ethyl ketone, methyl isobutyl ketone, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc. to prepare a varnish as needed, impregnated into a substrate such as glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, paper, etc. and heated and dried, and the obtained prepreg is hot-pressed to prepare a cured product of the curable resin composition of the present invention. The solvent used in this case is used in an amount of 10% to 70% by weight, preferably 15% to 70% by weight, in a mixture of the curable resin composition of the present invention and the solvent. In addition, if it is a liquid composition, the curable resin composition containing carbon fibers may be obtained directly, for example, by resin transfer molding (RTM).

[0187] In addition, the curable resin composition of the present invention can also be used as a modifier for film-type compositions. Specifically, it can be used to improve the flexibility of the B-stage. Such a film-type resin composition is obtained by preparing the curable resin composition of the present invention into the curable resin composition varnish and applying it on a release film, removing the solvent under heating, and then performing B-stage, thereby obtaining a sheet-like adhesive. The sheet-like adhesive can be used as an interlayer insulating layer of a multilayer substrate, etc.

[0188] The curable resin composition of the present invention can also be heated and melted, reduced in viscosity, and impregnated into reinforcing fibers such as glass fibers, carbon fibers, polyester fibers, polyamide fibers, and alumina fibers to obtain a prepreg. As specific examples thereof, glass fibers such as E glass cloth, D glass cloth, S glass cloth, Q glass cloth, spherical glass cloth, NE glass cloth, and T glass cloth can be listed, and inorganic fibers other than glass or organic fibers such as polyparaphenyleneterephthalamide (Kevlar (registered trademark), manufactured by DuPont), wholly aromatic polyamide, polyester, polyparaphenylene benzoxazole, polyimide, and carbon fibers can be listed, but they are not particularly limited to these. The shape of the substrate is not particularly limited, and for example, woven fabrics, non-woven fabrics, rovings, chopped strand mats, etc. can be listed. In addition, as the weaving method of the woven fabric, plain weave, basket weave, twill weave, etc. are known, and can be appropriately selected from these known weaving methods according to the target use or performance. In addition, it is preferred to use a glass woven fabric that has been subjected to fiber opening treatment or surface treatment using a silane coupling agent or the like. The thickness of the substrate is not particularly limited, and is preferably about 0.01 mm to 0.4 mm. In addition, a prepreg can also be obtained by impregnating the varnish into the reinforcing fiber and heating and drying it.

[0189] In addition, the prepreg can also be used to manufacture a laminate. The laminate is not particularly limited as long as it includes more than one prepreg, and it can also have any other layers. As a method for manufacturing a laminate, a generally known method can be appropriately applied without particular limitation. For example, when forming a laminate with a metal foil, a multi-stage press, a multi-stage vacuum press, a continuous forming machine, an autoclave forming machine, etc. can be used, and a laminate can be obtained by stacking the prepregs on each other and performing heating and pressurizing. At this time, the heating temperature is not particularly limited, preferably 65°C to 300°C, and more preferably 120°C to 270°C. In addition, the pressure of pressurization is not particularly limited. If the pressure is too large, the solid content of the resin of the laminate is difficult to adjust, and the quality is unstable. In addition, if the pressure is too small, the air bubbles or the adhesion between the layers deteriorate, so it is preferably 2.0MPa to 5.0MPa, and more preferably 2.5MPa to 4.0MPa. The laminated plate of the present embodiment includes a layer having a metal foil, and can be preferably used as a metal foil clad laminated plate described later.

[0190] The prepreg is cut into a desired shape, and after being laminated with copper foil or the like as needed, the curable resin composition is heated and cured while applying pressure to the laminate by a press molding method, an autoclave molding method, a sheet winding molding method, or the like, thereby obtaining an electrical and electronic laminate (printed wiring board) or a carbon fiber reinforced material.

[0191] The curable resin composition of the present invention can also be made into a resin sheet. As a method for obtaining a resin sheet from the curable resin composition of the present invention, for example, a method of coating a curable resin composition on a support film (support), drying it, and forming a resin composition layer on the support film can be cited. In the case of using the curable resin composition of the present invention for a resin sheet, it is important that the film softens under the lamination temperature conditions (70°C to 140°C) in the vacuum lamination method, and the circuit substrate is laminated, while showing the fluidity (resin flow) of the resin filled in the through holes or through holes present on the circuit substrate, and it is preferred to formulate the components to show such characteristics. In addition, in the obtained resin sheet or circuit substrate (copper sheet laminate, etc.), there is no phenomenon such as showing locally different characteristic values ​​due to phase separation, etc., and a certain performance is shown in any part, so the appearance uniformity is required.

[0192] Here, the through hole of the circuit board has a diameter of 0.1 mm to 0.5 mm and a depth of 0.1 mm to 1.2 mm, and it is preferable that the resin can be filled within the above range. In addition, when laminating both surfaces of the circuit board, it is ideal to fill about 1 / 2 of the through hole.

[0193] As a specific method for manufacturing the resin sheet, the following method can be cited: after preparing a varnished resin composition by blending an organic solvent, the varnished resin composition is applied to the surface of a support film (Y), and the organic solvent is dried by heating or hot blowing to form a resin composition layer (X).

[0194] As the organic solvent used here, it is preferred to use ketones such as acetone, methyl ethyl ketone, and cyclohexanone, acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate, carbitols such as cellosolve and butyl carbitol, aromatic hydrocarbons such as toluene and xylene, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc., and it is preferred to use a non-volatile component in a ratio of 30% by mass to 60% by mass.

[0195] In addition, the thickness of the resin composition layer (X) formed must be greater than the thickness of the conductor layer. The thickness of the conductor layer of the circuit substrate is in the range of 5 μm to 70 μm, so the thickness of the resin composition layer (X) is preferably 10 μm to 100 μm. In addition, the resin composition layer (X) in the present invention can also be protected by a protective film described later. By protecting with a protective film, dust or the like can be prevented from adhering to the surface of the resin composition layer or from being damaged.

[0196] The support film and the protective film can include polyolefins such as polyethylene, polypropylene, polyvinyl chloride, polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, polycarbonate, polyimide, and release paper or metal foils such as copper foil and aluminum foil. In addition, the support film and the protective film can also be subjected to demolding treatment in addition to matte treatment and corona treatment. The thickness of the support film is not particularly limited, and is 10 μm to 150 μm, preferably used in the range of 25 μm to 50 μm. In addition, the thickness of the protective film is preferably set to 1 μm to 40 μm.

[0197] The support film (Y) is peeled off after being laminated to the circuit substrate or after being heat-cured to form an insulating layer. If the resin composition layer constituting the resin sheet peels off the support film (Y) after heat-curing, the adhesion of dust and the like in the curing process can be prevented. In the case of peeling off after curing, the support film is subjected to a demolding treatment in advance.

[0198] In addition, a multilayer printed circuit board can be manufactured from the resin sheet obtained as described above. For example, in the case where the resin composition layer (X) is protected by a protective film, after these are peeled off, the layer (X) of the resin composition is laminated on one side or both sides of the circuit board by, for example, a vacuum lamination method, so that the layer (X) of the resin composition is in direct contact with the circuit board. The lamination method may be a batch type or a continuous type using a roller. In addition, the resin sheet and the circuit board may be heated (preheated) as needed before lamination. Regarding the lamination conditions, it is preferred to set the crimping temperature (lamination temperature) to 70°C to 140°C, and it is preferred to set the crimping pressure to 1kgf / cm 2 ~11kgf / cm 2 (9.8×10 4 N / m 2 ~107.9×10 4 N / m 2 ), preferably lamination is performed under reduced pressure of 20 mmHg (26.7 hPa) or less.

[0199] In addition, the curable resin composition of the present invention can be used to manufacture semiconductor devices. Examples of semiconductor devices include dual in-line package (DIP), quad flat package (QFP), ball grid array (BGA), chip size package (CSP), small outline package (SOP), thin small outline package (TSOP), and thin quad flat package (TQFP).

[0200] The curable resin composition of the present invention and its cured product can be used in a wide range of fields. Specifically, it can be used for various purposes such as molding materials, adhesives, composite materials, coatings, etc. Since the cured product of the curable resin composition described in the present invention shows excellent heat resistance and dielectric properties, it can be preferably used for sealing materials for semiconductor elements, sealing materials for liquid crystal display elements, sealing materials for organic electroluminescent (EL) elements, laminated boards (printed wiring boards, ball grid array (BGA) substrates, build-up substrates, etc.) and other electrical-electronic parts or composite materials for lightweight and high-strength structural materials such as carbon fiber reinforced plastics and glass fiber reinforced plastics, three-dimensional (three-dimensional, 3D) printing, etc.

[0201] Example

[0202] Next, the present invention will be described in more detail by way of examples. Hereinafter, parts are parts by mass unless otherwise specified. In addition, the present invention is not limited to these examples.

[0203] Various analytical methods used in the Examples are described below.

[0204] <Gel Permeation Chromatography (GPC)>

[0205] The weight average molecular weight (Mw) and the number average molecular weight (Mn) were calculated in terms of polystyrene using a polystyrene standard solution.

[0206] Gel permeation chromatograph (GPC): DGU-20A3R, LC-20AD, SIL-20AHT, RID-20A, SPD-20A, CTO-20A, CBM-20A (all manufactured by Shimadzu Corporation)

[0207] Column: Shodex KF-603, KF-602×2, KF-601×2

[0208] Linking eluent: tetrahydrofuran

[0209] Flow rate: 0.5ml / min.

[0210] Column temperature: 40℃

[0211] Detector: RI (differential refractometer)

[0212] <High Performance Liquid Chromatography (HPLC)>

[0213] Column: Inertsil ODS-2 (GL Sciences)

[0214] Detector: UV 274nm

[0215] Temperature: 40℃

[0216] Eluent: acetonitrile / water

[0217] Flow rate: 1.0ml / min

[0218] Injection volume: 5μl (concentration: about 10mg / 6ml)

[0219] Gradient program

[0220] Acetonitrile / water

[0221] 30 / 70 gradient at the beginning → 100 / 0 after 28 minutes

[0222] [Synthesis example 1]

[0223] While nitrogen was flushed into a flask equipped with a thermometer, a cooling tube, a fractionating tube, and a stirrer, 559 parts of aniline, 291 parts of α,α,α',α'-tetramethylbenzenedimethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 360 parts of toluene were added, and 63 parts of a 35% aqueous hydrochloric acid solution were added and stirring was started. While the water generated by dehydration was extracted together with the toluene, the internal temperature was raised to 160°C and the reaction was allowed to proceed for 15 hours. After cooling to room temperature, the extracted toluene and water were returned to the system, and 88 parts of a 30% aqueous sodium hydroxide solution were added for neutralization. Then, the organic layer was washed with water until the waste liquid became neutral, and then concentrated to obtain 458 parts of an aromatic amine resin (A1) represented by the following formula (5). The amine equivalent of the aromatic amine resin (A1) was 185 g / eq, and the softening point was 58.7°C. The GPC analysis (RI) showed that the n=1 isomer was 61%, and the 4,4'-(1,3-phenylenediisopropylidene) dianiline in the n=1 isomer obtained by HPLC analysis was 16.7%, so the 4,4'-(1,3-phenylenediisopropylidene) dianiline in the aromatic amine resin was 10.2%. The GPC chart of the obtained amine resin (A1) is shown in Figure 1 In the HPLC chart, Figure 2 In addition, 1 H-NMR ( 1 H-nuclear magnetic resonance, 1 H-NMR) chart (heavy chloroform) is shown in Figure 3 In. 1 A signal derived from an amino group was observed at 3.05 ppm to 3.65 ppm in the H-NMR chart.

[0224] [Chemistry 9]

[0225]

[0226] [Synthesis example 2]

[0227] In a flask equipped with a thermometer, cooling tube, Dean-Stark azeotropic distillation trap, and a stirrer, 147 parts of maleic anhydride, 300 parts of toluene, and 4 parts of methanesulfonic acid were added and heated under reflux. Then, a resin solution prepared by dissolving 197 parts of aromatic amine resin (A1) in 95 parts of N-methyl-2-pyrrolidone and 100 parts of toluene was added dropwise over a period of 3 hours while maintaining the reflux state. During this period, the condensed water and toluene that are azeotropic under reflux conditions are cooled and separated in the Dean-Stark azeotropic distillation trap, and the toluene as the organic layer is returned to the system, and water is discharged outside the system. After the addition of the resin solution is completed, the reflux state is maintained, and the reaction is carried out for 6 hours while performing a dehydration operation.

[0228] After the reaction is completed, water washing is repeated four times to remove methanesulfonic acid and excess maleic anhydride, and water is removed from the system by azeotropy of toluene and water under heating and reduced pressure below 70°C. Subsequently, 2 parts of methanesulfonic acid are added, and the reaction is carried out for 2 hours under heating and reflux. After the reaction is completed, water washing is repeated four times until the washing water becomes neutral, and then water is removed from the system by azeotropy of toluene and water under heating and reduced pressure below 70°C, and then toluene is completely distilled off under heating and reduced pressure, thereby obtaining maleimide resin (M-1). The softening point of the obtained maleimide resin (M-1) is 100°C and the acid value is 9 mgKOH / g.

[0229] [Example 1, Comparative Example 1]

[0230] Each material was dissolved and mixed in acetone in the proportion shown in Table 1 so that the solid content was 70% by mass. After pre-drying at 60°C for 30 minutes in a vacuum oven, it was pre-dried at 120°C for 30 minutes. Using 5 g of the obtained powder, vacuum pressing was performed while sandwiching it with a mirror copper foil (T4X: manufactured by Futian Metal Copper Foil Co., Ltd.), and hardened at 220°C for 2 hours. At this time, as a spacer, a buffer paper with a thickness of 250 μm was used, which was hollowed out in the center to a length and width of 150 mm. During the evaluation, a laser cutter was used to cut the test piece into the desired size as needed, and the evaluation was carried out. The evaluation results are shown in Table 1. In addition, the DMA graphs of Example 1 and Comparative Example 1 are shown in Figure 4 middle.

[0231] <Heat resistance (Dynamic Mechanical Analysis (DMA))>

[0232] Dynamic viscoelasticity tester: TA-instruments, DMA-2980

[0233] Measuring temperature range: -30℃~280℃

[0234] Heating rate: 2℃ / min

[0235] Frequency: 10Hz

[0236] Test piece size: Use cut into 5mm×50mm (thickness 0.2mm)

[0237] Tg: The peak point of tanδ (=loss modulus / storage modulus) is defined as Tg

[0238] <Water absorption test>

[0239] The sample was immersed in water at 25°C for 24 hours, and the water absorption rate was calculated from the weight difference before and after the water absorption test. The test was conducted with a sample size of 5 mm wide x 50 mm long and a thickness of 0.2 mm.

[0240] [Table 1]

[0241]

[0242] Acenaphthene: Made by JFE Chemical Co.

[0243] ·DCP: dicumyl peroxide (manufactured by Kayaku Akzo Chemicals)

[0244] From the results in Table 1, it was confirmed that Example 1 was superior in high heat resistance and low water absorption properties compared to the case where the maleimide compound was subjected to free radical polymerization alone. Figure 4 As a result, it was confirmed that Example 1 had excellent curability, as compared with the curing of the maleimide compound alone, no increase in elastic modulus at 300° C. or higher due to the uncured maleimide group was observed.

[0245] [Example 2, Comparative Example 2]

[0246] Each material was dissolved and mixed in acetone in the proportion shown in Table 2 so that the solid content was 70% by mass. After pre-drying at 60°C for 30 minutes in a vacuum oven, it was pre-dried at 120°C for 30 minutes. Using 5g of the obtained powder, vacuum pressing was performed while sandwiching it with a mirror copper foil (T4X: manufactured by Futian Metal Copper Foil Co., Ltd.), and hardened at 220°C for 2 hours. At this time, as a spacer, a buffer paper with a thickness of 250μm was used, which was dug into a length and width of 150mm. During the evaluation, a laser cutting machine was used to cut the test piece into the desired size as needed, and the evaluation was implemented. The evaluation results are shown in Table 1.

[0247] <Dielectric constant test / dielectric loss tangent test>

[0248] The test was conducted using a 10 GHz cavity resonator manufactured by ATE Co., Ltd. The test was conducted with a sample size of 1.7 mm in width x 100 mm in length and 0.1 mm in thickness.

[0249] <Heat resistance (DMA)>

[0250] Dynamic viscoelasticity tester: TA-instruments, DMA-2980

[0251] Measuring temperature range: -30℃~280℃

[0252] Heating rate: 2℃ / min

[0253] Frequency: 10Hz

[0254] Test piece size: Use cut into 5mm×50mm (thickness 0.1mm)

[0255] Tg: The peak point of tanδ (=loss modulus / storage modulus) is defined as Tg

[0256] [Table 2]

[0257]

[0258] Acenaphthene: Made by JFE Chemical Co.

[0259] ·DCP: dicumyl peroxide (manufactured by Kayaku Akzo Chemicals)

[0260] NC-3000L: Biphenyl aralkyl type epoxy resin (manufactured by Nippon Kayaku Co., Ltd.)

[0261] PN(H-1): Phenol novolac resin (manufactured by Meiwa Chemicals Co., Ltd.)

[0262] ·TPP: Triphenylphosphine (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0263] From the results in Table 2, it was confirmed that Example 2 was superior in high heat resistance and low dielectric properties compared to the epoxy resin composition used in the past.

[0264] [Examples 3 to 6, Comparative Examples 3 to 6]

[0265] After mixing the materials at the ratio shown in Table 3, the curability was evaluated by DSC. The evaluation results and the Q value and e value of each compound are shown in Table 3. The Q value and e value of the maleimide compound (M-1) are the values ​​of phenylmaleimide, which is a partial structure of the maleimide compound (M-1).

[0266] The DSC graphs of Examples 3 to 5 are shown in Figure 5 The DSC graphs of Comparative Examples 3 to 5 are shown in Figure 6 middle.

[0267] <Hardening property (differential scanning calorimeter (DSC))>

[0268] Differential scanning calorimeter: DSC6220 (manufactured by SII NanoTechnology)

[0269] Measuring temperature range: 30℃~330℃

[0270] Heating rate: 10℃ / min

[0271] Environment: Nitrogen (30mL / min)

[0272] Sample volume: 5mg

[0273] [Table 3]

[0274]

[0275] Acenaphthene: Made by JFE Chemical Co.

[0276] ·Allylbenzene: Made by Tokyo Chemical Industry Co., Ltd.

[0277] · Ethylene benzene: manufactured by Tokyo Chemical Industry Co., Ltd.

[0278] ·Butyl acrylate: manufactured by Tokyo Chemical Industry Co., Ltd.

[0279] Benzyl acrylate: manufactured by Tokyo Chemical Industry Co., Ltd.

[0280] The results in Table 3 show that Examples 3 to 5 have higher calorific value and better curability than the maleimide curing system of Comparative Example 3. Comparative Examples 4 and 5 have two peaks, indicating that alternating copolymerization of component (A) and component (B) is not smooth.

[0281] The curable resin composition, resin sheet and cured product thereof of the present invention can be preferably used for electric and electronic parts such as semiconductor sealing materials, printed wiring boards and build-up laminates.

Claims

1. A curable resin composition comprising: (A) a maleimide compound; and (B) Compounds having a Q value of 0 to 1.0 and an e value of -2.0 to 0.

7.

2. The curable resin composition according to claim 1, wherein The component (B) is a compound having an aromatic ring in its molecule.

3. The curable resin composition according to claim 1, wherein The component (B) is a compound represented by the following formula (4). [Chemistry 1] (In formula (4), X represents a functional group having an ethylenically unsaturated double bond or an acetylenically unsaturated triple bond, Ar represents a benzene ring or a naphthalene ring; Y represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms; and k represents an integer of 1 to 4.) 4. The curable resin composition according to claim 1, wherein The component (A) is a compound represented by the following formula (1). [Chemistry 2] (In formula (1), X independently represents any one of the structures represented by the following formulas (2-a) to (2-c); R represents a hydrogen atom, a hydrocarbon group having 1 to 10 carbon atoms, or a halogenated alkyl group; m represents an integer of 1 to 3, n is a repetition number, and the average value of n is n ave 1<n ave <10. ) [Chemistry 3] (In formula (2-a) to formula (2-c), * represents a bond to a benzene ring; R2 each independently represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms; and q each independently represents an integer of 1 to 4.) 5 . The curable resin composition according to claim 1 , further comprising a polymerization initiator. 6 . A resin sheet comprising the curable resin composition according to claim 5 and a support.

7. A cured product, which is a cured product of the curable resin composition according to claim 5.

Citation Information

Patent Citations

  • Binary developer

    JP1989029862A

  • Thermosetting resin composition

    JP1992359911A

  • New cyanate ester compound, flame-retardant resin composition and cured product thereof

    JP2005264154A

  • Resin composition for laminate, prepreg and laminate

    JP2009001783A

  • Allyl ether-modified biphenyl aralkyl novolac resin, allyl-modified biphenyl aralkyl novolac resin, method for producing same and composition using same

    WO2016002704A1

Cited By

  • Heat-resistant fluorine-free semi-alicyclic polyimide as well as preparation method and application thereof

    CN120795320A